2019
DOI: 10.3389/fimmu.2019.01372
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Lipopeptide Enhances Protective Immunity Against Helicobacter pylori Infection

Abstract: Over fifty percent of the people around the world is infected with Helicobacter pylori ( H. pylori ), which is the main cause of gastric diseases such as chronic gastritis and stomach cancer. H. pylori adhesin A (HpaA), which is a surface-located lipoprotein, is essential for bacterial colonization in the gastric mucosa. HpaA had been proposed to be a promising vaccine candidate against H. pylori infection. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…Mouse bone marrow cells were isolated from tibia and femurs, and then were cultured in RPMI 1640 medium containing 10% FCS, recombinant murine GM-CSF (6 ng/mL), and IL-4 (20 ng/mL) at 37 • C, 5% CO 2 . The non-adherent cells were removed on day 5 and adherent cells were cultured in a fresh complete medium for another 2 days (34). BMDCs (4 × 10 6 cells) were stimulated with either AbOMV (200 ng) or PBS for 48 h. After three washes, the cells were incubated with FITC-αCD11c, PE-αCD40, APC-αCD80, and PerCP/Cy5.5-αCD86 in the dark for 30 min at 4 • C. Flow cytometry data were acquired with a FACS Canto II (BD Biosciences).…”
Section: Generation Of Bmdcs and Facs Assaymentioning
confidence: 99%
“…Mouse bone marrow cells were isolated from tibia and femurs, and then were cultured in RPMI 1640 medium containing 10% FCS, recombinant murine GM-CSF (6 ng/mL), and IL-4 (20 ng/mL) at 37 • C, 5% CO 2 . The non-adherent cells were removed on day 5 and adherent cells were cultured in a fresh complete medium for another 2 days (34). BMDCs (4 × 10 6 cells) were stimulated with either AbOMV (200 ng) or PBS for 48 h. After three washes, the cells were incubated with FITC-αCD11c, PE-αCD40, APC-αCD80, and PerCP/Cy5.5-αCD86 in the dark for 30 min at 4 • C. Flow cytometry data were acquired with a FACS Canto II (BD Biosciences).…”
Section: Generation Of Bmdcs and Facs Assaymentioning
confidence: 99%
“…HpaA as an important adhesin consequently assists the life-long colonization of H. pylori to human stomach [17,18]. It has been proved that the amino acid sequences of HpaA were highly conserved [5,8]. However, the basis of binding specificity is still poorly understood due to lack of detailed information.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori must be able to colonize gastric epithelial cells to prevent the bacteria from being eliminated by mucus turnover and facilitate evasion from the immune system and further injure the gastric mucosa [2]. The adhesion of H. pylori to the gastric epithelium was mediated by the expression of adhesins and the receptor system [2][3][4], among which H. pylori adhesin (HpaA) as an outer mem-brane protein with approximately 29 kDa detected on the surface and flagellar sheath of H. pylori plays an important role in bacterial adhesion [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to native HpaA (nHpaA), the absence of lipid modification on rHpaA could be related to the weak immunostimulatory and protective effects. To simulate the N‐terminal lipidation structure of nHpaA, two new lipopeptides, LP1 and LP2, were synthesized by Xue et al 98 LP2 unlike LP1 were able to significantly promote DCs maturation, which may be associated with their ability to activate TLR‐2. By using real‐time PCR, the authors reported that H. pylori copy number in the group immunized intranasally with rHpaA + LP2 was significantly lower than in the control group ( P < .01).…”
Section: Vaccinesmentioning
confidence: 99%